AB0074 The Effect of Extracellular Vesicles on Human in Vitro Osteoclastogenesis in Health and in Arthritis. (15th July 2016) - Marton, N.; Kovacs, O.T.; Baricza, E.; Gyori, D.; Mocsai, A.; Meier, F.; Goodyear, C.S.; McInnes, I.B.; Buzas, E.I.; Nagy, G.S.
Abstract : Background: Extracellular vesicles (EVs) like microvesicles (MVs) and exosomes (EXOs) are released in an evolutionary conserved manner by cells. EVs mediate intercellular communication with the transmission of molecules from their parent cell to their targets. Objectives: Our objective was to investigate the effect of EVs on human in vitro osteoclastogenesis in healthy donors, rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients. Methods: Blood samples of healthy volunteers, RA patients and PsA patients with peripheral arthritis were collected. EVs were isolated by filtration and differential centrifugation. CD14+ cells were isolated from PBMCs by using positive selection, and the cells were stimulated with 50 ng/ml recombinant human M-CSF for 24 hrs. Then the samples were treated with 50 ng/ml recombinant human RANKL and blood-derived microvesicles or exosomes. After 7 days, the cells were fixed and stained for tartarate resistant acid phosphatase (TRAP). TRAP-positive cells with at least 3 nuclei were considered as osteoclasts and counted by using the ImageJ software. Results: Healthy and RA-derived exosomes significantly (p<0.01) inhibited osteoclast differentiation of the CD14+ cells from the same donors, while PsA-derived exosomes had a stimulatory effect (p<0.05) on osteoclastogenesis. In cross-induction experiments where EXOs and cells were interchanged between the 3 groups healthy (n=5) and RA (n=5) derived EXOs inhibited (p<0.01) the generation of osteoclasts in both groups but PsA (n=7) derived EXOs did not have an inhibitory effect. Microvesicles did not alter the number of mature osteoclasts in any groups. Conclusions: Our data suggest that EXOs profoundly regulate human osteoclastogenesis. PsA-derived EXOs stimulate, while healthy and RA-derived EXOs inhibit the osteoclast differentiation. Disclosure of Interest: None declared